Chapter Naturalizing Neuroethics? A Syncretic Approach - Shook, John R. (InTechOpen, 2019)
Neuroethics is uniquely situated to socially interpret what brain sciences are learning about social and moral cognition while helping society hold neuroscientific research and neurotechnological applications to firm moral standards. Both tasks, if they are to be pursued successfully, must find ways to closely relate the "neuro" with the "ethical." Keeping them apart has been the objective of nonnaturalist worldviews worried about scientism and reductionism, and now they complain about "neuroessentialism" and similar labels for dissolutions of agency and responsibility into mere brain activity. A nonnaturalistic neuroethics, on whatever metaphysical basis, insists that the biology of brains could not explain moral decisions or ground moral norms. We agree on that much, since the methodology of brain sciences presumes, and cannot replace, behavioral and psychological attributions of moral capacity and conduct. But the social and the neurological are always related through the anthropological; and that common basis is, not coincidentally, also where the ethical is grounded, as humanity upholds persons as bearers of moral worth and moral capacity. Neuroethics, by focusing on persons, need never resort to nonnaturalism to uphold what ultimately matters for ethics, and "naturalizing" neuroethics is also unnecessary for a humanity-centered neurobioethics.